Elucidating the effect of chain extenders substituted by aliphatic side chains on morphology and gas separation of polyurethanes. (5th January 2020) - Fakhar, Afsaneh; Sadeghi, Morteza; Dinari, Mohammad; Zarabadipoor, Mohammadmahdi; Lammertink, Rob
Graphical abstract: Highlights: PUU membranes were designed by different length-side chains based chain extenders. Shielding hard segment by side chains increased phase separation and reduced FFV. Dominant plasticizing effect increased permeability by longer side chain based PUU. The molecular designing of the PUUs allowed a further tuning of gas permeation. Abstract: Novel poly(urethane-urea) (PUU) membranes were developed as the aim of a structure-property relationship study to enhance gas permeation. Designing the PUUs was followed by three synthesized chain extenders with different length-alkyl side chains, polytetramethylene glycol, and isophorone and hexamethylene diisocyanates. The longest substituted PUU indicated higher phase separation and lower glass transition temperature. Pure and mixed gas permeabilities of prepared membranes grew as phase separation of PUU material increased, while fractional free volume decreased by lengthening the side chain of the PUUs. The reasons for this event were the migration of the side chains to the surface of hard domain, thereby shielding it and filling the soft/hard interface. Enhanced permeability of materials with l onger side chains is attributed to its plasticizing effect. The highest CO2 permeability (287 barrer) was obtained for the longest substituted PUU. The findings revealed an increase in gas permeation without a significant reduction of selectivity by longer substituted PUUs.